الإشراف التربوي ودوره فى تنمية الكفايات التعليمية لمعلم اللغة العربية بالمرحلة الثانوية من وجهة نظر المعلمين فى أمانة العاصمة صنعاء (الجمهورية اليمنية) : دراسة حالة - كرشوم، عبد الله يحيى هادي (Kulliyah of Education, International Islamic University Malaysia, 2012)
The role that educational supervisors play in the educational process is very important. In fact, educational supervisors play a most critical role in determining the success of teaching and learning so much so that the targeted aims of the process may not be achieved without their active participation. Being important role models and professional academic advisors, educational supervisors help teachers to acquire professional competencies that enable them to conduct teaching and learning effectively. In this case study, the role that educational supervisors play in helping Yemeni teachers acquire professional teaching competencies was examined from the perspectives of practicing teachers in selected secondary schools in the district of Shuoob, Sana'a. The effectiveness of the supervisors was examined in terms of enhanced performance and goals achievement as perceived by the practicing teachers. A series of semi-structured interviews were conducted with fifty-seven teachers of nine schools. In addition, the classroom teaching of these teachers was observed. The results point to many supervisory shortcomings and weaknesses, suggesting that the supervisors have not been playing their role accordingly. The results also suggest that supervisors function only as report writers of teachers' classroom performance, and do not help to develop and enhance their professional competencies. Based on the results, the study made several recommendations to assist educational supervisors and higher education authorities in improving the quality of educational supervision in Yemeni schools.